Reservoir Irrigation Operation Design Based on Dijkstra Algorithm Combined with ACO Algorithm - Jia, Baoping (Informatica, 2024)
In response to the problems of low resource utilization efficiency and imprecise management in traditional reservoir irrigation operation systems, a reservoir irrigation operation system combining Dijkstra algorithm and ant colony optimization algorithm is proposed. In the study, the improved Dijkstra algorithm is first used to optimize the irrigation operation path of the reservoir. On this basis, a more comprehensive reservoir irrigation operation system model is constructed by further combining ant colony optimization algorithm and improved Dijkstra algorithm. The results showed that the data processing accuracy, recall rate, and F1 value of the irrigation operation system model are 95.06%, 89.68%, and 85.07%, respectively. The length of the optimal path is 21.93 meters, and the annual average irrigation water consumption is 131 million m3. The data processing ability and irrigation water consumption prediction ability are better than the comparison method. This indicates that through reasonable operation design, the system model can better balance the irrigation, power generation, and various other needs of the reservoir, improve the efficiency of water resource utilization, and promote the sustainable development of agriculture and energy.